TRANSPARANSI PENGELOLAAN PADA LAPORAN KEUANGAN BUMDES TERHADAP LAPORAN ASET DESA (Studi Kasus BUMDES Desa Gunungrejo Kecamatan Singosari) - Karlina Apriliasari; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to find out how the process of transparency in the management of financial statements owned by BUMDes in reporting village assets. In terms of measurement or from the response of the community. For this study, researchers used an approach using interviews and documentation. The result of this research is that accounting must be carried out transparently in the form of financial statements owned by BUMDes. With this, BUMDes has not been fully transparent in its financial statements. in reporting village assets, the village has reported BUMDes assets in accordance with the guidebook, but BUMDes has not fully implemented transparency to the community.Keywords : LPJ transparency, asset transparency, channeling aspirations